Drone sperm (Apis mellifera) quality through the season in the argentinean pampa, an input for artificial insemination timing within selected lineages - Meroi Arcerito, Facundo Rene (2026)
Honey bee drone semen quality is influenced by environmental conditions, such as seasonal and resource changes in nectar and protein intake, and by genetic lineage and age. Thus, this study focuses on evaluating seasonal dynamics in sperm quality in selected lineages to identify the most suitable period for artificial insemination. The study was conducted on eight honey bee colonies belonging to the MeGA-PROAPI genetic improvement program, located at the Balcarce Agricultural Experimental Station (EEAB, INTA). The reproductive season was divided into three sampling times (T1: late November, T2: mid-January, T3: late February), and semen quality was evaluated using several techniques. Semen quality in honey bee drones varied throughout the reproductive season, peaking at mid-season (T2). Motility (ordinal scale 1–4), sperm viability (Eosin-Nigrosin and Eosin-Yellow stains), membrane integrity (HOST using distilled water), and sperm concentration all showed significant improvement at T2. Meanwhile, semen volume per drone, proportion of mature drones, and protein concentration remained stable across the season. Genetic lineages did not influence semen quality. These findings highlight T2 as the optimal time for semen collection and identify motility, viability (assessed with Eosin-Nigrosin stain), and the HOST test (using water at room temperature) as key variables to be considered as proxies of reproductive success in future artificial insemination studies on honey bees in this region.